Synbiotic açaí juice (Euterpe oleracea) containing sucralose as noncaloric sweetener: Processing optimization, bioactive compounds, and acceptance during storage. Issue 3 (3rd February 2021) - Freitas, Hildeane Veloso; Dos Santos Filho, Antonio Luiz; Rodrigues, Sueli; Abreu, Virgínia Kelly Gonçalves; Narain, Narendra; Lemos, Tatiana De Oliveira; Gomes, Wesley Faria; Pereira, Ana Lúcia Fernandes
Abstract : Abstract: This study aimed to evaluate the fermentation process of Lacticaseibacillus casei in the açaí juice, and to evaluate the addition of fructooligosaccharides and sucrose. The organic acids, anthocyanins, polyphenolic compounds, and antioxidant activity were also investigated during fermentation. Moreover, the impact of sucrose and sucralose on microbial viability and sensory acceptance of synbiotic products was evaluated during 42 days storage at refrigerated conditions. The conditions for synbiotic juice production were the initial pH of 6.1 and fermentation undertaken at 28 °C for 22 hr. During fermentation, the higher viability was obtained when a combination of 40 g/L of FOS+10 g/L of sucrose was used (9.70 ± 0.01 log CFU/mL). The lactic acid increased from 0.82 to 1.29 g/L during the fermentation while citric acid decreased from 1.05 to 0.75 g/L. The cyanidin‐3‐O‐rutinoside, polyphenolic compounds, and antioxidant activity increased. Thus, fermentation improved the functional value of the beverage. The L. casei viability reduced from 9.71 ± 0.04 to 8.90 ± 0.06 log CFU/ mL in the juice with sucrose, and from 9.71 ± 0.04 to 8.71 ± 0.14 log CFU/ mL in the juice with sucralose. Thus, the açaí juice is a viable matrix for the synbiotic food, which allows the viability maintenance during the storage. Regarding sensory acceptance, the internal preference mapping indicated an increase in the color preference with the storage of synbiotic juices. However, the flavor and overall acceptance reduced with storage. Nevertheless, the flavor and overall acceptance of juice with sucralose were better than the juice with sucrose. After 42 days of storage, penalty analysis revealed that beverage with sucrose showed a lack of sweet taste and excess of sour taste. Thus, a high‐quality açaí product with viable probiotic microorganism, high anthocyanins, and polyphenolic compounds contents could be obtained, which can be exploited for commercial use. Practical Application: Synbiotic açaí juice is a healthier alternative to consuming products containing this fruit. The inclusion of probiotic microorganisms and prebiotic fructooligosaccharides increased bioactive compounds contents during the shelf life of the juice. The sensory evaluation using the internal preference mapping revealed that the juice flavor with sucralose was better accepted than the juice formulated with addition of sucrose.